THE IMPLEMENTATION OF PESANTREN EDUCATION SYSTEM IN STUDENT INDEPENDENT LEARNING AT AR ROMMEL DORMITORY PESANTREN DARUL ULUM JOMBANG - Ali Muhsin (TAWASUT, 2020)
Abstract: The purpose of this study is to describe the Implementation of the Islamic Boarding School Education System in the Self-Reliance of Santri in Learning at the Ar Rommel Boarding House at the Darul Islamic Boarding School ‘Ulum Peterongan Jombang. This study aims to find out information about the pesantren education system in Ar Rommel's Dormitory. This research is a qualitative research,). Data collection techniques in this study was direct observation, interviews, and documentation. The results showed that: (1) The existence of Pesantren education system in Ar Rommel dormitory is reading a yellow book, recitation (fasholatan, istighosah, and surah in the Qur'an), reading the Qur'an. (2) the student independence is not merely assessed from their learning, but in the spirit of independence, including the category of independence such as increasing self-confidence (3) Implementation of supporting factors in the pesantren education system at the Ar Rommel dormitory, are responsibility and togetherness, teachers (asatidz ) comes on time. Furthermore, the implementation of the inhibiting factors of the pesantren education system in this dormitory is students who are late to join the teaching and learning process and teachers (asatidz) who cannot participate in teaching activities due to private events. Keywords: Islamic Boarding School Education System, Santri Independence Learning